Restoration, succession and climatic change - Wilson, J. Bastow (2004)
wo outstanding papers on restoration and succession are briefly discussed as model papers for the type of research papers Appl. Veg.Sci. should publish. The paper on restoration concentrates on the introduction of hay to a site in order to speed up the introduction of target species. The paper on succession discusses the importance of plant colonization ‘windows’ opened by extreme weather events for succession and for offering optimum periods for intervention in restoration practice. Some remarks are also made on the electronic availability of ecology papers.